PENGEMBANGAN SISTEM INFORMASI TERINTEGRASI UNTUK ADMINISTRASI JURUSAN MENGGUNAKAN TEKNOLOGI JAMSTACK - Palar, Michel; Masambe, Marcellino Semuel; Sendiang, Maksy; Waworuntu, Billy J. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic administration management in higher education institutions faces persistent challenges in data integration and workflow efficiency. The Department of Electrical Engineering at Politeknik Negeri Manado experiences fragmented administrative processes across unconnected platforms, data redundancy between modules, and the absence of a centralized real-time monitoring system for Final Project management. This study designs and builds an integrated web-based information system called E-Sekjur using JAMstack architecture (JavaScript, APIs, Markup) with Next.js 14 as the primary framework, Prisma ORM for type-safe database management, and PostgreSQL via Supabase as the cloud database. The Agile Development methodology enables iterative and adaptive feature implementation across three main modules: Interim Semester (SA), Academic Leave, and Final Project (TA). The system applies Role-Based Access Control (RBAC) for five user entities: Secretary of Department, Head of Study Program, Final Project Committee, Lecturer, and Student. Black Box Testing yielded 100% validity across 12 functional test scenarios. User Acceptance Testing (UAT) with 25 respondents (20 students, 5 lecturers) produced an overall acceptance score of 82.90%, categorized as Feasible and exceeding the 75% minimum threshold.